The Victims of Victims: Islamophobia in the South Korean Feminist Movement - Muquita, Namira Risqi Putri (Universitas Islam Internasional Indonesia, 2024)
This research attempts to introduce a new perspective on the complex relationships in South Korea's patriarchal society that produces